Perspectives From Emerging Researchers: What Next in EE/SE Research?. (17th March 2016) - Aguayo, Claudio; Higgins, Blanche; Field, Ellen; Nicholls, Jennifer; Pudin, Susan; Tiu, Sangion Appiee; Osborn, Maia; Hashemzadeh, Farshad; Lubuulwa, Kevin Kezabu; Boulet, Mark; Christie, Belinda A.; Mah, Jeremy
Abstract: Following the inaugural Australian Association for Environmental Education (AAEE) research symposium in November 2014, we — a group of emerging researchers in Environmental Education/Sustainability Education (EE/SE) — commenced an online collaboration to identify and articulate our responses to the main themes of the symposium. Identifying as #aaeeer, our discussions coalesced into four main areas that we felt captured not only some of our current research interests, but also 'under-explored' areas that need further attention and that also held the potential for meaningful and 'dangerous' contributions to EE/SE research and practice. These themes were: (1) uncertain futures, (2) traditional knowledges for the future, (3) community EE/SE, and (4) the rise of the digital, explorations of which we present in this article. By no means intended to capture all that is worth researching in this field, these themes, and this article, are deliberately presented by #aaeeer to spark discussions, as well as showcase an example of online collaboration between researchers in a number of countries.